Leitura em tempos da pandemia da COVID-19: uma análise da campanha #juntospelolivro - Mariano, Laura Andreoli (Universidade Federal de São Carlos, 2021)
As a society, we share a common representation of what it is to “be a reader”, that comes from a historically, socially and culturally constituted “discursive memory” about reading. In 2019, we witnessed an important downturn in the Brazilian economy, rising unemployment and a labor reform with relevant losses of rights on the part of workers. This economic crisis was accompanied, in 2020, by the announcement of the COVID-19 pandemic. In this scenario, several commercial sectors became even more fragile, such as the book sector. Then, the campaign #juntospelolivro was created, conceived by approximately 100 small and medium entrepreneurs in the book and publishing sector. This campaign had national circulation through Instagram and aimed to encourage reading habits and thus supporting the book trade. Besides, it consisted of a series of publications in the form of "posts" with this hashtag. With the analysis of these posts, we aim to analyze the discourses about reading and the reader mobilized in it. For this, we will analyze the verbal and non-verbal languages of these posts, as well as the argumentative strategies used. Our analysis is theoretically and methodologically based on principles of Discourse Analysis and Cultural History of Reading, as well as on studies by Brazilians researchers on reading. Among the results obtained in our analysis, we observed that, in these posts, we frequently resorted to the presentation of reading printed books as a healthy practice in this scenario of pandemic and social isolation. The posts of this campaign made special use of representations of reading as a form of “entertainment and hobby”, “therapy in times of pandemic”, and “company and antidote against loneliness” in times of social isolation. Thus, in a peculiar way to what we generally see about reading, we have more often found medical and therapeutic fields lexicon emerge in the characterization of this practice.
Reading in times of the COVID-19 pandemic: an analysis of the #togetherspelobook campaign
Keywords: Discursos sobre a leitura; Pandemia; Hashtag #juntospelolivro; Discourses about reading; Pandemic; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA